2008
DOI: 10.1007/s00210-008-0383-7
|View full text |Cite
|
Sign up to set email alerts
|

Coupling mode of receptors and G proteins

Abstract: Signaling via G-protein-coupled receptors (GPCRs) is crucial to many physiological and pathophysiological processes in multicellular organisms, and GPCRs themselves are targets for important drugs. Classical cell supplementation experiments suggest a collision coupling model, in which receptors and G proteins diffuse randomly within the cell membrane and interact only if receptors are activated. This model is also backed by kinetic and live cell imaging data. According to the challenging theory, receptors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 68 publications
0
43
0
Order By: Relevance
“…On the other hand, these findings also are consistent with more recent reports and proposed models, which suggest that the receptor/G protein complex remains intact after agonist activation. In this new model, receptors serve as signaling platforms that assemble multiple signaling components (e.g., heterotrimeric G proteins, RGS proteins, arrestins, GRKs, effectors) and, after receptor activation, G proteins do not dissociate but instead rearrange in situ to initiate signaling (Bü nemann et al, 2003;Hein and Bü nemann, 2009). Whether these receptor/G protein complexes internalize as a complex is unknown, although sustained coupling after internalization could result in sustained G protein signaling because PARs are constitutively activated after protease cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, these findings also are consistent with more recent reports and proposed models, which suggest that the receptor/G protein complex remains intact after agonist activation. In this new model, receptors serve as signaling platforms that assemble multiple signaling components (e.g., heterotrimeric G proteins, RGS proteins, arrestins, GRKs, effectors) and, after receptor activation, G proteins do not dissociate but instead rearrange in situ to initiate signaling (Bü nemann et al, 2003;Hein and Bü nemann, 2009). Whether these receptor/G protein complexes internalize as a complex is unknown, although sustained coupling after internalization could result in sustained G protein signaling because PARs are constitutively activated after protease cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…It is still unclear to what extent some of these time constant depend on the potentially diffusion-limited encounters between activated receptors and the G proteins (Lohse et al, 2014). Nevertheless, since these kinetics are reproducibly obtained with robustly overexpressed GPCRs (which should alleviate this concern; Hille, Dickson, Kruse, & Falkenburger, 2014), it appears that the rate of G protein activation is the rate-limiting step in effector activation, including GIRK (Hein & Bunemann, 2009;Jensen et al, 2009).…”
Section: Activation Kineticsmentioning
confidence: 96%
“…From these data, a concept emerges that involves catalytic, collision-coupling interactions between GPCRs and 324 G-proteins, so that one agonist-occupied receptor can activate many G-proteins, followed by noncatalytic, tightly coupled interactions between G-proteins and effectors (Vorobiov et al, 2000;Dascal, 2001;Lohse et al, 2008b;Hein and Bü nemann, 2009).…”
Section: Downstream Signalingmentioning
confidence: 99%
“…The deactivation of receptors, receptor/G-protein interaction, and G-protein activity seems to occur in this sequence; for example, in the case of A 2A -adenosine receptors and G s , the half-times of deactivation were Ϸ2 s for the receptor, Ϸ10 s for the receptor/G s interaction, and Ϸ25 s for G s (Hein et al, 2006). G-protein sensors have also been used to address the issue of receptor/G-protein precoupling versus collision coupling (see above; Hein and Bü nemann, 2009). By investigating the effects of various receptors present at different densities in CHO cells, Azpiazu and Gautam (2004) reported that different types of receptors (e.g., muscarinic and serotonin) shared common pools of G-proteins to which they seemed to have free access-a result that conflicts with a model of organized, preassembled receptor/Gprotein complexes.…”
mentioning
confidence: 99%